(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2019)
Background: Now a days, the patients are looking for hustle free and quick services in this fast growing world. In order to improve the satisfaction level of patients with health care provided at OPD, it is a requirement to have knowledge of the level of satisfaction of patients and feedback, about the services provided in the outpatient departments.The study design was conducted to assess patients satisfaction with health care services provided at outpatient department. Materials and Methods: This study was conducted at outpatient department of a public hospital ie. Chattogram Medical College Hospital (CMCH) and A Private Hospital ie. Chattagram Maa Shishu-O-General Hospital (CMSOGH) Chattogram, commencing from 1st January 2011 to 30th June 2011 and sample size was 106. Convenient type of sampling technique was followed.Data was collected by using questionnaire containing structured questions. Results: The mean age of the patients was 35 years ± 6.9.In case of receiving services from these two hospitals, the highest percentage was among the age group 30-39 years which is about 36.66% and lowest among the age group 50-59 years which is about 16.98%. Maximum patients were not satisfied with the hospital environment. Regarding OPD ticket fee 86.67% patients in CMCH were satisfied whereas only 26.09% patients were satisfied in CMSOGH.54.72% patients were satisfied with sympathy and respect shown to them by doctors. Privacy during examination (71.70%) investigation from outside hospital (60.38%) and not satisfied with consent before examination (79.25%) in total of CMCH & CMSOGH patients.55.26% female patients were satisfied with attitude of the doctor whereas 51.47% male patients are satisfied. 53.57% Secondary to graduate level patients were satisfied and Illiterate to primary level group were 52.00%. Conclusion: This study on patient satisfaction with health care services provided at OPD will help the relevant policy makers and planners in making appropriate plan and policies to reduce the problems and improve their health.Moreover, the study will reveal much useful information that will help physicians in Bangladesh to be more patient friendly; the researcher thinks in a nutshell that these are the justification of the study. JCMCTA 2018 ; 29 (2) : 57-62